Digital Media Literacy as a Motivational Strategy Learning Interest and Digital Competence in Pitu Riase 3 State Junior High School Students: Literasi Media Digital sebagai Strategi Motivasi Minat Belajar dan Kompetensi Digital pada Siswa SMP Negeri 3 Pitu Riase - Sarimin, Amaluddin; Prabowo, Mulyo; Firdaus, Muh. (SABIQ: Jurnal Sosial dan Bidang Pendidikan, 2024)
This study aims to identify and describe: 1) Strategies for utilizing digital media literacy in motivating the learning interest of SMP Negeri 3 Pitu Riase students, and 2) Digital competence of SMP Negeri 3 Pitu Riase students in managing knowledge and accessing the information on the internet. This research is descriptive research with a qualitative approach. The findings of this study are as follows. 1) The strategy to motivate students' interest in learning at SMP Negeri 3 Pitu Riase in using digital media begins with knowing the interest in learning from learning outcomes and the existence of motivation from parents. Then to motivate interest in learning, this is done in several ways including, namely, innovating in learning, compiling teaching materials, and applications that are appropriate to the situation and conditions. The need for the effectiveness of digital media in motivating students' learning interest can be seen from its benefits in the learning process, namely, helping passive students and helping present information and instructions. 2) The digital literacy competence of SMP Negeri 3 Pitu Riase students still lacks understanding related to digital competence. This is because of the four indicators of digital literacy competence, only one can be understood by students, namely the ability to search on the Internet (Internet Searching), while the ability to use Hypertextual Navigation, Evaluating Information Content (Content Evaluation) and Compilation of Knowledge (Knowledge) Assembly) still needs improvement and understanding related to digital competence.